On the publication year of Sericini genera and species described by Brenske in “Die Serica-Arten der Erde” (Coleoptera: Scarabaeidae: Sericinae) - Ahrens, Dirk; Bezděk, Aleš (Zootaxa, 2024)
The year of publication of Brenske’s species and genera described in his opus “Die Serica-Arten der Erde” is updated following up an overlooked delay of some of the fascicules of the Berliner Entomologische Zeitschrift, namely the volumes 42, 43, and 46. This change affects 201 species group names and 20 genus group names, many of which have been revised in the past three decades, but no change of priority of other names occurred. The spelling of Mericserica oberthueri Brenske, 1899 is corrected.